The Federal Trade Commission's mandated Four Loko labeling fails to facilitate accurate estimation of alcohol content by college students. (3rd July 2020) - Rossheim, Matthew E.; Yurasek, Ali M.; Greene, Kaylin M.; Gonzalez-Pons, Kwynn M.; Barry, Adam E.; Thombs, Dennis L.; Trangenstein, Pamela J.; Nelson, Candace; Cavazos, Tammy; Treffers, Ryan D.; Jernigan, David H.
ABSTRACT: Background: Four Loko, the leading supersized alcopop brand, is a pre-mixed alcoholic beverage containing up to 5.5 standard alcoholic drinks in a can. In 2013, the Federal Trade Commission (FTC) mandated the addition to Four Loko cans of a label indicating its alcohol content in standard drinks, presented as "alcohol per serving" and "servings per container." Objective: The current study investigated whether college students accurately estimate the alcohol content in cans of Four Loko bearing the FTC mandated labels. Method: Undergraduate student drinkers ( n = 833; 51.6% women) in three states (Florida, Montana, and Virginia) were provided an empty Watermelon Four Loko can and asked to determine the number of standard drinks it contained, using 12-ounce regular beer (Budweiser) equivalents. In Florida and Virginia, Watermelon Four Loko contains 4.70 standard alcoholic drinks; in Montana, it contains 3.13. Results: More than 60% of Florida students and more than 70% of Virginia students underestimated Four Loko's alcohol content by one or more standard drinks, compared to 45% of Montana students. Multivariable logistic regression analysis found the following variables were associated with greater odds of underestimating Four Loko's alcohol content by one or more standard alcoholic drinks: being female (AOR = 2.2), having never seen nor heard of Four Loko (AOR = 1.9), and residing in Florida (AOR = 1.7) or Virginia (AOR = 2.8) versus Montana. Conclusions: Students were far less likely to underestimate alcohol content for 8% alcohol-by-volume (abv) cans compared to those with higher alcohol concentrations. Thus, policies restricting supersized alcopops' abv may help consumers better estimate their alcohol content.